Find CF if (D+D¹-2) (D+2D¹-2)2 = 0
"\\text{General partial differential equation is}\\\\\n(c_0D^n+c_1D^{n-1}D^{'}+\u2022\u2022\u2022+c_nD^{'n})z=0\\\\\n\\text{comparing the given differential equation and the general pde},\\\\\n\\text{for }(D+D'-2)(D+2D'-2)^2=0\\\\\nwe \\,know, when \\,aD+bD'+c=0\\\\\n\\text{Then, CF is}\\space e^{-\\frac{c}{a}x}\\phi(bx-ay).\\\\\n\\text{by comparing}\\\\\n\\text{Therefore, CF for this differential equation is }\\\\e^{2x}(\\phi(x-y))+e^x(x\\phi_1(2x-y)+\\phi_2(2x-y))"
Comments
Leave a comment